Design Web-Based Smart Parking System Prototype for Efficient Management of Parking Spaces - Wijaya Kuntoro; Mudofar Baehaqi; Vidya Ikawati (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2021)
Along with technological advances, the increase in the number of motorized vehicles that have occurred in recent decades has led to an increasingly pressing problem of parking availability. This is especially the case in densely populated urban areas, where drivers often spend a long time looking for an empty parking space. The purpose of this research is to facilitate the process of finding a parking space for users. The Smart Parking System aims to make it easier for parking lot users to find a place to park without spending a lot of time. Parking monitoring in the Smart Parking System is carried out by using the website as a display media on the monitor. This system consists of an ultrasonic sensor as a vehicle detector and NodeMCU as a microcontroller. The design of this system shows that it has not worked perfectly because it still has problems and deficiencies in the prototype system. Due to differences in the NodeMCU type, it is difficult to connect to the access point. For the solution, NodeMCU must be connected one by one to the Arduino IDE serial monitor so that it can be connected to the access point. The results of this research trial, the sensor can detect parked vehicles and can send data to NodeMCU. It takes 1 second to send data from each sensor to NodeMCU and it takes 4 seconds to loop from 4 sensors. Meanwhile, sending data from NodeMCU to the database takes 15-20 seconds from each NodeMCU, this can happen because it is influenced by the signal.